The constitutionality of the early prorogation of the public service concessions - Sanguiné, Odone (2019)
This article deals with the early prorogation of the public service concessions. It is justified, among other reasons, because the early prorogation of numerous concessions was recently authorized in Brazil by several normative acts, so that the theoretical and practical interest for the theme really is very great at this moment in our country. Therefore, the purpose of this article is to verify whether the early prorogation is or is not compatible with the Brazilian Constitution. And the research hypothesis is that this species of prorogation is constitutional. The method of approach of the theme is the deductive, and the research method, the bibliographic. Finally, the main conclusion of this article is that the early prorogation of the public service concessions is compatible with the Brazilian Constitution, which confirms the research hypothesis.